Blood derived eye drops for the treatment of cornea and ocular surface diseases. Issue 4 (August 2017) - Giannaccare, Giuseppe; Versura, Piera; Buzzi, Marina; Primavera, Laura; Pellegrini, Marco; Campos, Emilio C.
Abstract: The use of blood derived eye drops for the treatment of ocular surface disorders has become increasingly popular in recent years. The mechanism of action is the stimulation of cellular proliferation and migration by supplying an active mixture of growth factors and cytokines at the ocular surface, thus mimicking the function of the lacking natural tears. Blood derived eye drops have been used in the last decades for the treatment of a variety of ocular surface diseases, including mainly dry eye disease, persistent corneal epithelial defect, corneal ulcer, ocular surface burn, recurrent corneal erosion and limbal stem-cell deficiency. Among overall blood derived eye drops, both autologous (from the patients themselves) and homologous (from donors) products exist, with different advantages and disadvantages. Autologous serum, obtained from the patient's own peripheral blood, is the first introduced and most commonly used product. Despite several randomized clinical trials showed its safety and efficacy, a recent Cochraine meta-analysis failed to show significant results due to low evidence. Homologous sources including allogeneic serum obtained from healthy donors, and umbilical cord blood serum collected at the time of delivery, are efficient alternatives, especially when autologous serum therapy is contraindicated or not appropriate. Platelet-derived eye drops are prepared and used in various but poor standardized preparations, namely platelet-rich plasma, plasma rich in growth factors, and platelet lysate. Future perspectives of blood-derived products include the introduction of tailored eye drops, screened for the proper content of growth factors and cytokines according to each patient and ocular surface disease.